Menyikapi Penyebaran Narkoba (Sosialisasi Penanggulangan Narkoba) - Munari Munari; Mohammad Riski Borman; Nasrullah Nasrullah; Nawawi Natsir; Nasir Manggasing; Facrul Reza (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service article aims to describe drug prevention outreach efforts in Palu City through an educational, collaborative, and participatory approach. The outreach program was launched in response to the increasing number of drug abuse cases, particularly among adolescents. Through outreach, volunteer formation, and the involvement of various community elements, the results of this activity indicate increased knowledge, changes in attitudes, and a significant decrease in drug distribution cases. This article also outlines the key challenges and innovative strategies implemented as a community service model in drug-prone areas.